A Brazilian Adam Smith: Cairu as the Founding Father of Political Economy in Brazil at the beginning of the 19th century - Almeida, Paulo Roberto (MISES: Interdisciplinary Journal of Philosophy, Law and Economics, 2018)
Adam Smith’s seminal work, The Wealth of Nations, was introduced to Brazilian readers by an autodidatic “economist”, José da Silva Lisboa, at the beginning of the 19th century. The paper intends to reconstruct the reception of Smith’s ideas in Brazil (and Portugal), through the early works of José da Silva Lisboa. He was a remarkable intellectual, liberal by instinct besides a government official, who was largely responsible for the “economic opening” of Brazilian ports to foreign trade (decreed by the Portuguese Regent, Prince D. João, in 1808, at his arrival in Brazil). He was honored with the title of Viscount of Cairu (who became the patron of the Brazilian economists in the 20th century). He translated, incorporated, copied and transformed many Smithian ideas in his books (published in Portugal and Brazil, by Imprensa Régia), adapting them to a colonial economy and a backward agricultural environment. He suggested, among other original features, the existence of a fourth factor of production (besides land, labor and capital): knowledge, which could be considered an anticipation of modern conceptual evolution in economic thinking.